Chitosan-based mucoadhesive patches for buccal delivery of olmesartan in hypertension treatment - Nikhate, Ram; Patil, Sanjay (Journal of Applied Pharmaceutical Research, 2025)
Background: Delivering poorly soluble drugs like Olmesartan (OMS) effectively remains a key challenge due to low oral bioavailability and extensive first-pass metabolism. To address this, buccal patches incorporating chitosan were developed as an alternative route to enhance systemic absorption. Methodology: A series of buccal patch formulations (F1–F17) was prepared using combinations of chitosan, polyvinyl alcohol (PVA), HPMC K4M, and Eudragit RL via solvent casting. These patches were evaluated for uniformity in weight, thickness, pH, mechanical strength, folding endurance, and mucoadhesion. Structural and morphological assessments were carried out using X-ray diffraction and SEM. Ex vivo and in vivo studies explored drug release, permeation, pharmacokinetics, and mucosal safety. An HPLC method was employed for accurate quantification, and stability was assessed under both accelerated and ambient conditions. Results and Discussion: The optimised patch (F2) demonstrated consistent physical properties, high flexibility, and strong mucoadhesion. XRD patterns confirmed the amorphous dispersion of OMS in the polymer matrix, aiding solubility. Drug release was sustained over 12 hours, and permeation studies showed controlled transport across the buccal membrane. In vivo results revealed a substantial improvement in drug bioavailability via buccal delivery (83.2%) compared to oral administration (30.2%). Histological analysis indicated no signs of tissue irritation. Patches maintained integrity and potency throughout six months of storage. Conclusion: The findings support the buccal patch as a viable, non-invasive platform for enhancing OMS delivery, offering improved therapeutic efficiency and patient compliance.